Quantitative electroencephalogram (QEEG) Spectrum Analysis of Patients with Schizoaffective Disorder Compared to Normal Subjects - Moeini, Mahdi; Khaleghi, Ali; Amiri, Nasrin; Niknam, Zahra (Iranian journal of psychiatry, 2014)
The aim of this study was to achieve a better understanding of schizoaffective disorder. Therefore, we obtained electroencephalogram (EEG) signals from patients with schizoaffective disorder and analyzed them in comparison to normal subjects. Forty patients with schizoaffective disorder and 40 normal subjects were selected randomly and their electroencephalogram signals were recorded based on 10-20 international system by 23 electrodes in open- and closed-eyes while they were sitting on a chair comfortably. After preprocessing for noise removal and artifact reduction, we took 60- second segments from each recorded signals. Then, the absolute and relative powers of these segments were evaluated in all channels and in 4 frequency bands (i.e., delta, theta, alpha and beta waves). Finally, Data were analyzed by independent t-test using SPSS software. A significant decrease in relative power in the alpha band, a significant decrease in power spectra in the alpha band and a significant increase in power spectra in the beta band were found in patients compared to normal subjects (P < 0.05). The predominant wave in the centro-parietal region was the beta wave in patients, but it was the alpha band in normal subjects (P = 0.048). Also, the predominant wave of the occipital region in patients was the delta wave, while it was the alpha wave in normal subjects (P = 0.038). Considering the findings, particularly based on the significant decrease of the alpha waves in schizoaffective patients, it can be concluded that schizoaffective disorder can be seen in schizophrenia spectrum.